Built to last: lysosome remodeling and repair in health and disease - Zoncu, Roberto; Perera, Rushika M. (Trends in cell biology, 2022)
Lysosomes play major roles in growth regulation and catabolism and are recognized as critical mediators of cellular remodeling. An emerging theme is how the lysosome is itself subjected to extensive remodeling in order to perform specific tasks that meet the changing demands of the cell. Accordingly, lysosomes can sustain physical damage and undergo dramatic changes in composition following pathogen infection, accumulation of protein aggregates, or cellular transformation, necessitating dedicated pathways for their repair, remodeling, and restoration. In this review, we focus on emerging molecular mechanisms for piecemeal remodeling of lysosomal components and wholesale repair and discuss their implications in physiological and pathogenic challenges such as cancer, neurodegeneration, and pathogen infection. The lysosome is a catabolic organelle that is the end point of degradative pathways including endocytosis, phagocytosis, and autophagy.Lysosomal damage can result from accumulation of undigested substrates within the lumen, changes in lipid composition of the membrane, loss of pH and/or membrane potential, and outright rupturing of the lysosomal limiting membrane by mechanical or chemical insults.Lysosomes are subject to continuous remodeling and repair via the action of dedicated signaling pathways, which detect lysosomal stress and dysfunction and trigger both transcriptional and post-translational programs that adjust lysosomal function in a compensatory manner.Prompt repair of lysosomal injury is important for numerous cell types and especially essential for neuronal cells, while enhanced biogenesis and plasticity are emerging as key adaptive mechanisms in cancer cells.